Tinjauan Maslahah Mursalah Terhadap Perlindungan Tenaga Kerja Dalam UU Cipta Kerja - Nurkholidah, Susi; Andala, Angga; Amalia, Ridha (Universitas Islam Negeri Raden Intan Lampung, 2022)
This research reveals the changing sounds of articles in the Job Creation Law and analysis according to Maslahah Mursalah. The purpose of this research is to find out the parts of the Job Creation Law in Indonesia that are detrimental and have a bad impact on one of the parties (labor). Indonesian government has simplified through an omnibus law in which there are several laws that have been trimmed to make it more efficient. The concept of this omnibus law is in the form of a job creation law that has 11 clusters, one of which regulates employment. Then socialization and study are needed to avoid these conflicts and losses. This research uses a normative juridical approach method, namely research by examining library materials (library research). The conclusion of this study is that changes in the regulations of several articles contained in the Job Creation Law still have a bad impact on workers or workers if applied to the company and its employees. This is inconsistent with the theory of maslahah mursalah, which is to attach importance to the lives of many people or more of detriment than benefits to labor.Key words: Maslahah Mursalah, Job Creation Law, Labor Protection